Imelda (Unico Entertainment, 2004)
Imelda marks the first time that Mrs. Marcos agreed to tell her story. This feature documentary details her rise from humble provincial origins with a combination of guile, ambition and beauty to become one of the riches and most powerful women in contemporary history and one of the few known by her first name.